EFFECT OF FOLIAR SPRAY WITH " TECNOKEL AMINO Ca- B" SOLUTION AND SALICYLIC ACID ON SOME CHEMICAL PROPERTIES OF PERSIMMON (Diospyros kaki L.) CV.FUYU - Marir, Muhannad Rajab; Al- Hayani, Ali Mohammed Abd (Journal of agricultural, environmental and veterinary sciences, 2019)
The study was carried out during the growing season 2017 in one of the private orchards in Diyala Governorate/ Al- Khalis district/ Zanbour village, to study the effect of spraying with nutritious solution and Salsicylic acid on some chemical properties of twenty years homogeneous size and growth fuiyu khaki trees planted at 3.5 x 3.5 m. A global experiment was applied using RCBD with four replicates (one tree for experimental unit). The experiment included the use of two- factor effect: the Tecnokel Amino Ca- B solution with four concentrations (0, 2, 4 and 6 ml L- 1) and Salicylic acid (SA) in three concentrations (0, 200, 400 mg L- 1), The results were statistically analyzed using the SAS program and the means were compared using Duncan’s multiple rangetest at a probability level of 0.05. The results can be summarized as follows: The spray with 6 ml L- 1 nutritional solution significantly in TSS(%) and TSS/ TA, carotenoids content in fruit which gave the highest values reached 24.89, 44.40, 0.146% Respectively. The same concentration was significantly distinguished by giving the least acidity percentage and lowest content of tannins in fruits was 0.665, 0.838 Respectively. Salicylic acid spraying at 400 mg L- 1 gave the highest values of TSS , TSS/ TA and carotenoids in fruits was 24.18, 38.50, 0.123% Respectively. The same concentration treatment gave lowest percentage of TA in fruit juice was 0.665 compared with untreated control treatment, whereas the treatment content of the tannins, the concentration of 200 mg L- 1 gave the lowest content of tannins content was 1.12% for the treatment of water spray treatment. The interaction between the nutritious solution at 6 ml L- 1 and salicylic acid spray at 400 mg L- 1showed significant differences over the reast treatments TSS(%), TSS/ TA ratio and the carotenoids content in the fruits was 25.63, 50.42, 0.154% Respectively. The same treatment mentiond above achieved the lowest content of TA in the fruits was 0.509. Interaction between 6 ml L- 1 nutrition solution with 200 mg L- 1 salicylic acid treatment gave the lowest fruit tannins content was 0.694% compared with untreated control treatment.